Pre-empting Plateau: The nature of topological transitions in foam - HUTZLER, STEFAN; WEAIRE, DENIS LAWRENCE (Institute of Physics, 2007)
When the area of a face in a dry foam approaches zero in some quasistatic processes, Plateau?s rules dictate that there must be an instability. This is more subtle than generally supposed.We argue that it is generally pre-empted, that is, the instability arises before an unstable multiple vertex is formed. Experiments and calculations which simulate Plateau?s wire frame experiments support this view.
PUBLISHED
Keywords: Condensed Matter Physics; unstable multiple vertex